Low-Loss Mechanically Tunable Resonator and Phase Shifters in Groove Gap Waveguide Technology - Karami Horestani, Ali; Shaterian, Zahra; Mrozowski, Michal (IEEE access, 2022)
This research is focused on the design and realization of high-performance high-power variable phase shifters in groove gap waveguide technology. Specifically, it is shown that the unique characteristic of groove gap waveguides, which is its proper operation without the need for electrical connection between the top and bottom sections of the waveguide, can be used to design mechanically tunable devices. Using the proposed method, a mechanically tunable cavity resonator and phase shifters with a wide range of achievable phase shifts are presented. To validate the concept, a phase shifter with 540 degrees relative phase shift at 15 GHz is designed, fabricated, and measured. Moreover, a multi-layer version of the proposed phase shifter with stationary feed ports and improved performance is presented.